Queering Christianity: Sexual and Spiritual Identity Navigation in LGBTTQIA+ Folks At Trinity Western University and the Implications for Practitioners of Psychotherapy - Esau, Christie (Université d'Ottawa / University of Ottawa, 2017)
This thesis considers the lived experiences of LGBTTQIA+ students who currently attend or have attended Trinity Western University (TWU), a private Christian university that requires all staff, students and faculty to sign a community covenant expressing marriage is between a man and a woman. Importantly, TWU is currently seeking to start a law school, which faces great opposition due to TWU’s historical and current exclusion of queer folks. Subsequently, this thesis draws on data gathered from six qualitative interviews with current or past TWU students who also identify as LGBTTQIA+, women and/or gender non binary with the hope of making space for those folks while also offering criticisms and recommendations for TWU to consider. Additionally, this thesis seeks to provide clinical recommendations for counsellors and psychotherapists as they work to support folks at the intersections of spiritual and sexual identity in an affirmative and supportive manner.
Keywords: Christian; Queer; Spirituality; Sexuality; Counselling; Psychotherapy; Identity; Lesbian; Gay; Bisexual; Gender; Trinity Western University; Two-Spirit; Non-binary; Qualitative; Interview